Implementation of sustainable marketing concept in a company as a prerequisite to survive on global market - Petković Nebojša; Milovanović Goran (Marketing (Beograd. 1991), 2019)
Modern economy, based on knowledge and embodied in large capital and powerful corporations capable of imposing their interests and influences throughout the world, is evolving towards the consolidation, unification and birth of new forms of colonialism and domination. The emergence of new technologies, new products and markets is a new challenge for companies that are forced to question their marketing approaches and adjust strategies in the unstable business environment. Sustainable development in the global "economy of planned product obsolescence* presupposes the review of ethical and environmental principles as well as a shift towards consumer-oriented sustainability. The new approach starts from the consumer and his concern for himself, the community and nature. The aim of this paper is to prove, based on the systematization and analysis of scientific knowledge from relevant scientific literature and contemporary business practice, that in the global economy, companies' perspectives increasingly depend on their ability to innovate in their marketing approaches and responses to consumer, society and nature demands. In order to reach such evidence, the authors analyze the characteristics of the global economy, the relationships between corporate social responsibility and globalization, the mission of sustainable development in the global economy and the role of responsible consumption.